Overview of Nursing Diagnoses in Respiratory Emergency Cases at the Emergency Department of Andi Makkasau Regional General Hospital, Parepare City - Bahriah; Henrick Sampeangin; Heni Silvia; Yunita Palinggi; I Melda Imel; Muhammad Asri (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Respiratory emergencies are very critical conditions and require rapid treatment in the Emergency Department (ER). An accurate nursing diagnosis is important to support patient safety and recovery. The purpose of this study was to determine the description of nursing diagnoses that are often made in patients with respiratory emergencies in the ER of Andi Makkasau Hospital, Parepare City. This study used a quantitative descriptive design with a total sampling technique. Data were taken from patient medical records throughout 2024 and analyzed univariately. The results showed that the three most common nursing diagnoses were ineffective breathing patterns (63.77%), impaired gas exchange (34.49%), and ineffective airway clearance (1.74%). Ineffective breathing patterns were the most common problem. Nurses in the ER are expected to continue to improve their ability to recognize and handle respiratory emergencies.